2005
DOI: 10.1159/000083873
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Postoperative Crohn’s Disease

Abstract: At 1 year after a first resection, up to 80% of patients show an endoscopic recurrence, 10–20% have clinical relapse, and 5% have surgical recurrence. Smoking is one of the most important risk factors for postoperative recurrence. Preoperative disease activity and the severity of endoscopic lesions in the neoterminal ileum within the first postoperative year are predictors of symptomatic recurrence. Mesalamine is generally the first-line treatment used in the postoperative setting but still provokes considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 73 publications
0
10
0
2
Order By: Relevance
“…Up to 80% of all patients suffering from Crohn's disease undergo surgery at least once during the course of their disease, stricture formation being the most common indication in a high proportion of them. Moreover, recurrence of stricture formation is common at the site of surgical anastomosis (25,31,102).…”
Section: Intestinal Fibrosis In Humans: the Clinical Problemmentioning
confidence: 99%
“…Up to 80% of all patients suffering from Crohn's disease undergo surgery at least once during the course of their disease, stricture formation being the most common indication in a high proportion of them. Moreover, recurrence of stricture formation is common at the site of surgical anastomosis (25,31,102).…”
Section: Intestinal Fibrosis In Humans: the Clinical Problemmentioning
confidence: 99%
“…The development of explicit criteria of appropriateness of the use of various postoperative treatment regimens will be a useful aid to clinical decision making in this context. This review is an updated version of a prior publication published as a preparatory work for the European Panel on the Appropriateness of Crohn’s Disease Therapy (EPACT) held in 2004 [1] and entirely replaces the earlier publication.…”
Section: Introductionmentioning
confidence: 99%
“…This was subsequently expanded manually to include references contained in review articles and references suggested by the panelists. The selected studies were arranged hierarchically according to evidence-based medicine criteria and commented on in a series of review articles [2,3,4,5,6,7,8,9,10,11]. References to the primary studies are to be found in those articles.…”
Section: Methodsmentioning
confidence: 99%